2018
DOI: 10.1186/s40634-018-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Implicit video feedback produces positive changes in landing mechanics

Abstract: BackgroundImplicit (IF) and explicit (EF) feedback are two motor learning strategies demonstrated to alter movement patterns. There is conflicting evidence on which strategy produces better outcomes. The purpose of this study was to examine the effects of reduced IF and EF video feedback on lower extremity landing mechanics.MethodsThirty participants (24 ± 2 years, 1.7 ± 0.1 m, 70 ± 11 kg) were randomly assigned to three groups: IF (n = 10), EF (n = 10), and control (CG) (n = 10). They performed twelve box-dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…An external visual focus of attention can ensure visuospatial demands during training and implicit learning can reduce the cognitive demands for motor control to potentially enhance training. [37][38][39][40]…”
Section: Motor Learning Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…An external visual focus of attention can ensure visuospatial demands during training and implicit learning can reduce the cognitive demands for motor control to potentially enhance training. [37][38][39][40]…”
Section: Motor Learning Principlesmentioning
confidence: 99%
“…121 While few studies have examined the behavioral impacts of implicit cues for sports medicine, Popovic et al demonstrated improved landing biomechanics with implicit feedback relative to explicit/no feedback. 40 Thus, instructional language informed by implicit learning may augment visual perturbation training by modulating sensorimotor neural activity and potentially increasing neural efficiency by reducing the cognitive load of learning injury-resistant movement strategies. The newly freed cortical resources may enable athletes to more readily attend to visual distractors during high-level sport (e.g., the ball, opponents) while maintaining neuromuscular control.…”
Section: Implicit Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…El tercer aspecto importante en el programa PNM de lesiones LCS-SC es la educación y la retroalimentación en el aterrizaje. La instrucción de estímulos verbales, visuales, de video o retroalimentación de manera implícita mediante una proyección visual pueden facilitar el aprendizaje del gesto motor (Gilchrist et al, 2008;Olsen et al, 2005;Popovic et al, 2018;Steffen et al, 2008). Este factor resulta muy importante debido a la elevada complicación de la tarea, que adicionalmente se incrementa por los factores intrínsecos de la mujer (p.ej.…”
Section: Discussionunclassified
“…Risk of musculoskeletal injury, specifically anterior cruciate ligament (ACL) injury, is associated with decreased neuromuscular control and coordination during dynamic activities (Griffin et al, ; Hewett et al, ; Hewett, Torg, & Boden, ; Ireland, ; Krosshaug, Slauterbeck, Engebretsen, & Bahr, ; Zazulak, Hewett, Reeves, Goldberg, & Cholewicki, ). Advances in 3D motion analyses and force platforms have permitted the assessment of neuromuscular coordination using the drop vertical jump (DVJ) (Chaudhari et al, ; Cruz et al, ; DiCesare, Kiefer, Bonnette, & Myer, ; Doherty et al, ; Earl, Monteiro, & Snyder, ; Etnoyer, Cortes, Ringleb, Van Lunen, & Onate, ; Ford, Myer, & Hewett, , ; Hewett et al, ; Limroongreungrat & Boonkerd, ; McLean et al, ; Paterno et al, ; Popovic et al, ; Schmitz et al, ; Taylor et al, ). During the landing phase of the DVJ, tri‐planar hip, knee, and ankle motion that results in the knee collapsing toward the midline, or “dynamic valgus,” is quantified via an external peak knee abduction moment (pKAM) (Carson & Ford, ; Ford, Myer, & Hewett, ; Ford et al, ; Ford, Shapiro, Myer, Van Den Bogert, & Hewett, ; Galloway et al, ; Hewett et al, ; Malfait et al, ; Myer et al, , , ).…”
Section: Introductionmentioning
confidence: 99%